THE THEMATICAL VARIETIES OF UZBEK FALK LEGENDS AND THEIR EXPRESSION IN THE TRANSLATION - Ruziyev Nodir Qayumovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The thematical varieties of Uzbek falk legends and their expression in the translation are analyzed as per interpretation in the literature. Mainly the legends related with the professions and meals are discussed.